Painless Labor in Pakistan: Gaps, Barriers, and Missed Opportunities for Maternal Health - Abbas, Sana (Utan Kayu Publishing, 2025)
This narrative review examines the “silent suffering” of women in Pakistan who experience unmanaged labour pain despite major advances in obstetric analgesia globally. Drawing on approximately 25 empirical, policy and survey sources, the review synthesises evidence on the availability, distribution and use of painless labour services—including epidural analgesia and nitrous oxide (Entonox)—through the lens of the WHO Health Systems Framework and, where relevant, the “three delays” model. Findings reveal a highly inequitable landscape in which painless labour is concentrated in a few urban tertiary and private facilities, constrained by infrastructural gaps, high out-of-pocket costs, persistent shortages and maldistribution of anaesthesiologists, and underutilisation of midwives. Demand-side barriers include low awareness, widespread misconceptions about risks, and socio-cultural and religious narratives that normalise labour pain and limit women’s autonomy. These structural and cultural constraints collectively undermine Pakistan’s commitments to respectful maternity care and universal health coverage. The review concludes with policy and practice recommendations, including investments in public-sector capacity, integration of labour analgesia into benefit packages, task-shifting selected modalities to midwives, and community engagement to address myths and affirm women’s right to pain relief.